Pengaruh Penempatan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Bintang Shafwan - Azzahra, Fatimah; Kamil, Musthafa (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The purpose of this study is to identify how PT. Bintang Shafwan manages their human resources, specifically regarding the influence of "Work Placement and Work Discipline on Employee Performance of PT. Bintang Shafwan". In addition, as important as it is to have a job placement that matches your skills and work experience, you can foster interest in work that suits the needs of the company. And work discipline that has been appropriate such as the rules made by the company can improve the overall performance of the company. The method used in this study is a quantitative method, in this study using a saturated sample with a total of all populations as a sample of 50 employees of PT. Bintang Shafwan. The research method is quantitative statistics. Data analysis includes data quality tests, namely validity and reliability tests, classical assumption tests, t-tests and f tests. As the results in this study show that work placement has a positive and partially significant influence on employee performance with t count 2.169 > t table 2.011 and significance values 0.035 < 0.050. Work discipline has a positive and significant influence partially on employee performance with t count 2.367 >t table 2.011 and significance values 0.022 < 0.050. So, the implication in this study, work placement and work discipline that are already regular and in accordance with company rules must be maintained because they can have a positive impact on employee performance.